The Hungry Rural India: Their Cacophony and Silence (Global Journal of Science Frontier Research, 2020)
In spite of being a nation mostly dependent on agriculture, the scenario of Indian agriculture and its farmers are very poor. Not only the farming community, the non farming community of rural India is also living under a miserable situation. They are even sometimes facing huge struggle to arrange their bread and butter. They are the bleak background behind the silver screen; the ground zero level really of shinning India. Our present study was conducted in two rural localities: one is farm locality and the other is non farm locality. There were 21 independent variables for the farm sector and 19 were for the non farm sector, while the dependent variable(hunger) remaining the same. From each locality 75 respondents were chosen (150 respondents in total) and they were being interviewed through a structured interview schedule. The data were analysed through step down regression method and it was revealed that the parameters of hunger for farm sector were very much different from that of the non farm sector though it was linked with a wire of ignorance and silence.
Keywords: farm sector; non farm sector; hunger; silence